DYNAMICS FEATURES PАRODONTAL DISEASE IN PATIENTS WITH ЕNDOPARDONTAL POCKETS OF INFECTION IN THE COMBINED TREATMENT - P. V. Moroz; V. A. Prohodnaja; A. S. Lomova (Медицинский вестник Юга России, 2014)
Purpose:to examine characteristics of parodontitis with periapical infection and the dynamics of parodontal status in the combined treatment of periodontal and endodontal.Materials and methods:34 were patient with infectious pathology of parodontal disease: 16 patients with parodontitis and availability simultaneously with signs of chronic periodontitis top (Group 1) and 18 of the patients with parodontitis and lack of periapical infections (Group 2). An index score of parodontal tissue in dynamics of combined endodontic and parodontic treatment.Results:In Group 1 after the elimination of infection in the parodentium apical hygiene indexes (plaque and tartar), bleeding, gingival and parodontal indexes declined with greater intensity and in a shorter time compared with 2 group, reflecting a more favourable dynamics of gums, parodontal hygiene and hard tissues of the mouth with the combined endoparodonta treatment l.Conclusion: endodontic treatment is a necessary part of a comprehensive treatment of endoparodontal syndrome. Termination of pathological processes in the apical periodontal parodontal status of marginal saniruet, helps reduce inflammatory reactions in the parodontium of high gradient with bone regeneration of alveoli in the short term.